Occupancy estimation and modeling : inferring patterns and dynamics of species occurrence /: inferring patterns and dynamics of species occurrence. (2017) - MacKenzie, Darryl I; Nichols, James D; Royle, J. Andrew; Pollock, Kenneth H; Bailey, Larissa; Hines, James E
No abstract available